2009
DOI: 10.1016/j.apmr.2008.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of the Beck Depression Inventory-II in Persons With Traumatic Brain Injury

Abstract: Objectives Our objective was to examine the Beck Depression Inventory-II (BDI-II) in a traumatic brain injury (TBI) sample using a receiver operating characteristic (ROC) curve to determine how well the BDI-II identifies depression. An ROC curve allows for analysis of the sensitivity and specificity of a diagnostic test using various cutoff points to determine the number of true positives, true negatives, false positives, and false negatives. Design This was a secondary analysis of data gathered from an obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 26 publications
(38 reference statements)
2
45
0
Order By: Relevance
“…17 Symptoms of PTSD and depression were assessed using the PostTraumatic Stress Disorder Checklist Military (PCLM) 18 and Beck Depression Inventory (BDI). 19,20 The neurologic examination was conducted by research staff (J.D., D.R., T.M., O.A.). Severity of balance impairment was tested using the Balance Error Scoring System (BESS).…”
Section: Participants Screening Of 230 Us Active Duty Military Servimentioning
confidence: 99%
“…17 Symptoms of PTSD and depression were assessed using the PostTraumatic Stress Disorder Checklist Military (PCLM) 18 and Beck Depression Inventory (BDI). 19,20 The neurologic examination was conducted by research staff (J.D., D.R., T.M., O.A.). Severity of balance impairment was tested using the Balance Error Scoring System (BESS).…”
Section: Participants Screening Of 230 Us Active Duty Military Servimentioning
confidence: 99%
“…Finally, one may argue that reading self-report scales to patients or applying them in the same occasion of SCID-I administration may have overestimated reporting of depressive symptoms. Again, this cannot be completely ruled out, but it seems unlikely, as discussed by other authors, 10 because determining the diagnostic properties of the scales was not an objective at the time of the interviews. Moreover, in a previously mentioned study, 12 the interviewers read the HADS to all subjects and the scale performed poorly.…”
Section: Discussionmentioning
confidence: 91%
“…28 One previous study 8 Questionnaire-9. Another study 10 reported an AUC of 0.88 for the Beck Depression Inventory-II in a sample consisting of military veterans with mainly mild and moderate TBI; this sample also had other distinctive characteristics, such as a high incidence of posttraumatic stress disorder and older age. In a community sample 9 of patients with mild to severe TBI (45% of severe cases), an AUC of 0.82 was found for the HADS depression subscale; in this study, the definition of depression was broader, with the inclusion of dysthymia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purposes of this study, a MHD includes depression, anxiety, and/or PTSD symptoms that meet the following study criteria. A Beck Depression Inventory-II (BDI-II) [26][27] score of 17 or higher, a Beck Anxiety Inventory (BAI) [28][29] score of 8 or higher, and/or meeting the lenient criteria [30] on the Clinician-Administered Posttraumatic Stress Disorder Scale (CAPS) classified Veterans in the MHD group. Criteria to be classified as having mTBI included reports indicating currently active symptoms (e.g., headache, sensitivity to light, and lack of concentration) where symptoms were corroborated by performance on neuropsychological tests.…”
Section: Testing Batterymentioning
confidence: 99%